Políticas públicas de igualdade racial: Trajetórias e mudança institucional no governo federal de 2000 a 2014 - Tatiana Dias Silva; Paulo Du Pin Calmon; Suylan de Almeida Midlej e Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This text investigates how public policies focused on racial equality were inserted in the governmental agenda and how they were implemented by the Brazilian federal government from 2000 to 2014. The research strategy was a case study, using process tracing to analyze the facts in this period. Based on this tool, a timeline was developed, consisting of three periods and a background section. The first period (2000 to 2002) refers to the time of preparation for the Durban Conference in 2001 and its immediate effects. In the second period (2003-2009), the institutionalization of the racial equality policy within the federal government was marked by the rise of the government of the Workers' Party (PT) and by the creation of a dedicated department on ministerial level - Secretaria de Políticas de Promoç\~ao da Igualdade Racial (the Secretariat of Policies for the Promotion of Racial Equality). The last period (2010-2014) incorporates the policy consolidation, in which developed norms and decisions established the legitimacy of the undertaken policies and allowed their expansion. To investigate each period in relation to the stated aims, questions and assumptions, the research was divided into three non-linear steps. In the first stage, the focus is to trace the timeline, with the main events of each period and with the main causal mechanisms that led to the institutional change. The second stage focuses on qualifying the institutional change, characterizing its main aspects. In the third stage, it tries to identify how the categories of the various protagonists, contexts and institutions acted in the process of institutional change. The investigation was based on documental, bibliographical and interview research. It is concluded that the process of insertion of racial equality policies in the Brazilian federal government in the period from 2000 to 2014 was promoted by causal mechanisms such as international pressure, institutional tension and normative validation, configuring a layered institutional change trajectory, which also lead towards processes of change by conversion and by drift.
Keywords: Z18; 330; racial equality; institutional change; causal mechanisms; process tracing